Automated intruder detection from image sequences using minimum volume sets - Ahmed, Tarem; Wei, Xianglin; Ahmed, Supriyo Sabbir; Pathan, Al-Sakib Khan (© 2012 International Journal of Communication Networks and Information Security, 2016)
This article was published in the International Journal of Communication Networks and Information Security [© 2014 IJCNIS] and The Article's website is at: http://www.ijcnis.org/index.php/ijcnis/article/view/88